Sports Diplomacy and Governance: Football Agents & FIFA’s Regulations - Mensah, Cocou Marius (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
Over the past few decades, the regulation of football agents has undergone a significant transformation. From a flexible “intermediary” regime to regulatory responsibility under national associations, the decentralised model has generated legal uncertainty, uneven standards, and concerns regarding transparency and accountability. To address this issue, the Fédération Internationale de Football Association (FIFA) adopted the FIFA Football Agent Regulations (FFAR), reintroducing a mandatory global licensing framework that includes a standardised examination, eligibility requirements, and compliance mechanisms. This article examines the legal and regulatory evolution from deregulation to re-regulation and analyses the ongoing legal challenges raised by FIFA’s rules. It argues that the new examination and licensing system, particularly under the 2025 FFAR framework, structures the profession, enhances integrity, and strengthens governance. While contested, the reform represents a necessary step toward professionalisation, regulatory coherence, and the protection of players and market stability in international football.